The Cerebral β‐Amyloid Angiopathies: Hereditary and Sporadic - Zhang‐Nunes, Sandy X. (Brain Pathol, 2006)
We review the clinical, radiologic, and neuropathologic features of the hereditary and sporadic forms of cerebral amyloid angiopathy (Caa) associated with vascular deposition of the β‐amyloid peptide. amino acid substitutions at 4 sites in the β‐amyloid precursor protein, all situated within the β‐amyloid peptide sequence itself, have been shown to cause heritable forms of Caa. the vascular diseases caused by these mutations are associated primarily with cerebral hemorrhages, white matter lesions, and cognitive impairment, and only variable extents of the plaque and neurofibrillary pathologies characteristic of alzheimer disease. sporadic Caa typically presents 20 or more years later than hereditary Caa, but is otherwise characterized by a comparable constellation of recurrent cerebral hemorrhages, white matter lesions, and cognitive impairment the clinical, radiologic and pathologic similarities between hereditary and sporadic Caa suggest that important lessons for this common age‐related process can be learned from the mechanisms by which mutation makes β‐amyloid tropic or toxic to vessels.